(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article discusses the specific features and directions of developing the methodological skills and professional competence of future teachers based on a cognitive approach, methods for developing the methodological skills of future teachers in processing and presenting information, innovative and traditional methods that require their application, and these methods